Modern human sperm freezing: Effect on DNA, chromatin and acrosome integrity - Tahereh Rahiminia; Akram Hosseini; Morteza Anvari; Saeed Ghasemi-Esmailabad; Ali Reza Talebi (Elsevier, 2017)
Objective: Presence of vitrification method in sperm freezing and the introduction of solid surface vitrification beside rapid freezing in vapour, opens an easy and safe way to help infertility centres. While the effects of cryopreservation on motility, morphology and viability of sperm are documented, the question of the probable alteration of sperm DNA, chromatin and acrosome integrity after freezing and thawing procedures in different methods is still controversial. Materials and methods: Normal sample were collected according to WHO strict criteria. Sperm suspensions were mixed 1:1 with 0.5 M sucrose and divided into four equal aliquots for freezing: fresh, nitrogen direct immersion vitrification (Vit), solid surface vitrification (SSV) and in vapour (Vapour). Sperm suspensions were transferred into a 0.25 ml sterile plastic. Then straw was inserted inside the 0.5 ml straw. For thawing, the straws were immersed in a 42 °C water bath. Beside the sperm parameters, we assessed the acrosome reaction by double staining, chromatin integrity by toluidine blue (Tb) and chromomycin A3 (CMA3) and DNA integrity by terminal deoxynucleotidyl transferase dUTP nick end labelling (TUNEL) respectively. Results: In progressive motility, the highest rate occurred in Vit (39.9 ± 13.3). Moreover, the lowest rate of immotile sperm was in Vit (32.7 ± 16.3). In normal morphology, the group Vit was similar to the fresh, while SSV and Vapour were significantly different from the fresh. The percentage of acrosome-reacted sperms was more in Vit (81.3 ± 10.2) than the fresh group. TUNEL+ results showed that DNA fragmentation was significantly increased in Vit (p-value = 0.025). While in SSV and Vapour results were comparable to fresh. There was a significant correlation between TUNEL+ and normal morphology, TB, CMA3 and presence of intact acrosome. Conclusion: Sperm in Vapour was healthier in terms of DNA, chromatin and acrosome integrity. In contrast of higher motility and normal morphology; DNA, chromatin and acrosome integrity were decreased in Vit. However, these findings were more acceptable in SSV or Vapour.